Does Corporate Governance Influence Firms’ Credit Ratings? Evidence from India - Kaur, Jaspreet; Dey, Soma (Indian Journal of Finance, 2025)
Purpose : Credit rating was an indicator of a firm’s creditworthiness, evaluated by rating agencies using firm-level characteristics combined with their judgment and experience. The literature hypothesized that a firm’s governance mechanism influenced its likelihood of default and the risk to debtholders. In this context, this study examined the impact of corporate governance on credit ratings. Methodology : One hundred thirty-one non-financial Indian listed firms that received ratings from India’s top four credit rating agencies from 2011 to 2021 formed the study sample. Ordered probit regression and marginal effect analysis were used to investigate the influence of selected corporate governance variables on credit ratings. Findings : The results revealed that increased board size, gender diversity, institutional investor ownership, promoter shareholding, and independence of audit and compensation committees make it more likely for firms to achieve higher credit ratings. In contrast, an increase in insider ownership and CEO role duality were associated with lower credit ratings. Board characteristics and ownership structure emerged as the most critical governance categories, with board size and gender diversity having the most significant impact on credit ratings. Practical Implications : The findings demonstrated that good governance improves credit ratings, helping to mitigate the information asymmetry problem faced by investors. Originality : The research provided evidence on less explored corporate governance factors in determining credit ratings in an emerging market like India.